(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
Reading is a cognitive activity that involves the eyes and the brain and many complex processes. According to a number of researchers such as Davies (1995), learning to read requires bringing together a number of actions involving the eyes, the brain, and the psychology of the mind that do not occur naturally. Teaching reading for first year learners in an Algerian middle school class is very important and strategic. Actually, teaching them how to read requires some essential processes. These are: word recognition, phonics, phonemic awareness, oral language, vocabulary and prior knowledge. So the components of a reading instruction for those learners include the above processes and more. The aim of this paper is to suggest a reading instruction for an Algerian first year middle school class. Keywords- word recognition , PHONICS, PHONEMIC AWARENESS, ORAL LANGUAGE, PRIOR KNOWLEDGE.